A Study of Watching Behavior and Participation in Satellite Television Programs - Lealaphan, Acharapan; Launglaor, Wisanu (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2014)
Thailand started television broadcasting in 2495. Because of technological advances, television broadcasting has changed, in particular the growth of satellite television. Currently 45% of Thais watch satellite TV. This justifies studying the watching behavior and involvement with satellite television programs. The purpose of this study is to find out the watching behavior of the residents of Metropolitan Bangkok and their involvement with satellite television programs. This research showed that the majority of residents were female, mostly students aged between 15-25 years, with a monthly income between ฿5,001 to ฿15,000. Most households are equipped with only one receiver box. The most popular brand is True Life + (red dish).The main reasons for having selected this brand are: variety of channels, quality of signal, low price, favorite programs and no monthly fee. The top five favorite programs are: movies, music, dramas, news, and sports. The top three channels are: True Music, Major, and Bang. 63.81% of the sample did not have any involvement in satellite television programs. Behaviors of men and women regarding participation in satellite television programs are not different.